2018
DOI: 10.22437/jkmj.v2i2.6553
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Antara Obesitas Dan Aktivitas Fisik Dengan Kejadian Hipertensi Di Puskesmas Rawasari Kota Jambi Tahun 2018

Abstract: Hipertensi yang juga dikenal sebagai tekanan darah tinggi, merupakan kondisi pembuluh darah yang terus-menerus menaikkan tekanan di atas normal. Secara global, penyakit kardiovaskular menyumbang sekitar 17 juta kematian per tahunnya, hampir sepertiga dari total. Dari jumlah tersebut, komplikasi hipertensi menyumbang 9,4 juta kematian di seluruh dunia setiap tahunnya. Hipertensi adalah salah satu penyebab kematian dini di seluruh dunia dan masalah ini semakin berkembang. Pada tahun 2025, diperkirakan 1,56 milia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 0 publications
1
3
0
4
Order By: Relevance
“…The prevalence close to results in this study can be seen in a research by Integrated Development Post for Non-Communicable Disease of Port Health Office (POSBINDU PTM KKP) Bandung in 2016 on 202 samples showing that the proportion of overweight and obesity was 54.9% 6 . This is also in accordance with research which found that 53.61% of respondents are obese 19 .…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The prevalence close to results in this study can be seen in a research by Integrated Development Post for Non-Communicable Disease of Port Health Office (POSBINDU PTM KKP) Bandung in 2016 on 202 samples showing that the proportion of overweight and obesity was 54.9% 6 . This is also in accordance with research which found that 53.61% of respondents are obese 19 .…”
Section: Discussionsupporting
confidence: 93%
“…However, it was below the results of the 2018 Riskesdas measurement, which was 33.12% for North Sulawesi 3 . The proportion of Cont... Table 2 : The Relationship of Incidence of Hypertension Based on Age, Obesity, and Gender this research is still far from the proportion obtained by Anggraini et al, 62.89% of the subjects had high blood pressure or hypertension and results of Posbindu PTM KKP Bandung in 2016 which found that the proportion of stage 1 hypertension was 41.7% 6,19 The results of this study indicate a significant relationship between obesity and hypertension in Tomohon. This is in accordance with several previous studies conducted in various regions in Indonesia.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Aktivitas fisik yang dilakukan secara teratur akan melatih otot jantung dan resistensi perifer sehingga mengurangi kekakuan pembuluh darah dan meningkatkan daya tahan jantung serta paru-paru sehingga dapat menurunkan tekanan darah. 14,15,16 . Individu yang memiliki aktivitas fisik yang rendah mempunyai risiko menderita hipertensi sebesar 30-50% lebih besar jika dibandingkan dengan individu yang memiliki aktifitas fisik tinggi.…”
Section: Hubungan Aktivitas Fisik Dengan Kejadian Hipertensi Pada Lan...unclassified